Rascal - North, Sterling, 1906-1974.; Schoenherr, John (USA: Dutton Childrens Books, 1963)
Newberry Honor
Keywords: North, Sterling -- Biography; Authors, American -- 20th. century -- Biography; Rascal(racoon).; Racoons -- Wisconsin -- Biography; Country life -- Wisconsin; Schoenherr, John, ill